Immunological effect of administration of sequential doses of Haemophilus influenzae type b and pneumococcal conjugate vaccines in the same versus alternating limbs in the routine infant immunisation schedule: an open-label randomised controlled trial. - Iro, M; Khatami, A; Marshall, A; Pace, D; Voysey, M; McKenna, J; Campbell, D; Attard-Montalto, S; Finn, A; White, C; Faust, SN; Kent, A; et al. (Lancet, 2015)
BACKGROUND: The use of different limbs for the administration of sequential doses of an intradermal rabies vaccine was shown to result in reduced vaccine immunogenicity. We aimed to assess whether this phenomenon also occurs with routine infant vaccines. METHODS: In this open-label, randomised, controlled study, eligible healthy infants 6-12 weeks of age recruited through five clinical trials units (four in the UK and one in Malta) were randomly assigned in a 1:1 ratio to two vaccination groups: consistent limb or alternating limb. Infants in the consistent limb group received the diphtheria-tetanus-acellular pertussis-inactived polio-Haemophilus influenzae type b combined vaccine (DTaP-IPV-Hib) at 2, 3, and 4 months of age, and the pneumococcal conjugate vaccine (PCV13) at 2, 4, and 12 months, all administered to the right leg. Infants in the alternating limb group received DTaP-IPV-Hib in the left leg at 2 months and in the right leg at 3 and 4 months; and PCV13 in the left leg at 2 months, in the right leg at 4 months, and in the left arm at 12 months. All infants in both groups received the combined H influenzae type b and capsular group C Neisseria meningitidis tetanus toxoid conjugate vaccine (Hib-MenC-TT), administered in the left leg at 12 months. Randomisation was achieved by randomly generated codes, with permuted block size of 30, and was stratified by study site. Group allocation was not masked from study staff and parents of participants after enrolment, but group allocation was masked from laboratory staff assessing blood samples. The current study was a prespecified secondary objective of a parent phase 4 trial that assessed the induction of immunity following varying schedules of vaccination with glyco-conjugate capsular group C Neisseria meningitidis (Men C) vaccines in infancy. The objective of the current study was to compare the immunogenicity and reactogenicity of vaccines delivered in either consistent or alternating limbs. Immunogenicity was assessed by comparing serum IgG geometric mean concentrations at 5, 12, 13, and 24 months, analysed per protocol. This study is registered with ClinicalTrials.gov, number NCT01129518. FINDINGS: Between July 5, 2010, and Aug 1, 2013, we enrolled 509 infants and randomly allocated them to the consistent limb group (n=254) or the alternating limb group (n=255). Anti-H influenzae type b anti-polyribosylribitol phosphate IgG geometric mean concentrations were lower in the consistent limb group than in the alternating limb group at 5 months (consistent limb 0·41 μg/mL [95% CI 0·31-0·54] vs alternating limb 0·61 μg/mL [0·45-0·82]; p=0·0268) and at 12 months (0·35 μg/mL [0·28-0·43] vs 0·50 μg/mL [0·40-0·62]; p=0·0136). Anti-tetanus toxoid antibody IgG geometric mean concentrations were lower in the consistent limb group (1·63 IU/mL [95% CI 1·40-1·90]) than in the alternating limb group (2·30 IU/mL [1·97-2·68]) at 13 months (p=0·0008) and at 24 months (0·44 IU/mL [0·37-0·52] vs 0·61 IU/mL [0·51-0·73]; p=0·0074). Anti-pneumococcal IgG geometric mean concentrations were similar between both groups at all timepoints. The proportions of participants who had adverse events did not differ between the two groups. INTERPRETATION: Use of different (alternating) limbs for sequential doses of routine infant vaccines does not reduce, and might enhance, immunogenicity. The underlying mechanism for this finding warrants further research. FUNDING: NIHR Oxford Biomedical Research Centre and GlaxoSmithKline Biologicals.